Investigating the Effectiveness of Top-Down and Bottom-Up Strategies in Developing Listening Skills Among Second-Year English Education Students - Muhammad Arbain; Dewi Nur Kumala Sari; Tiara Sekar Kinasih (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study investigates the effectiveness of top-down and bottom-up listening strategies in improving EFL students’ listening comprehension. Listening is a crucial skill in second language acquisition, yet it remains challenging due to limited exposure to authentic input and various processing difficulties. The objective of this study was to examine whether the integration of top-down and bottom-up strategies significantly improves students’ listening achievement. A pre-experimental quantitative design with a one-group pretest–post-test model was employed. The participants were 20 second-year students of the English Education Study Program at Islamic University of Kalimantan Muhammad Arsyad Al-Banjari, selected through total sampling. Data were collected using a listening comprehension test administered as both pretest and post-test, and analyzed using descriptive statistics and a paired-samples comparison. The findings revealed an improvement in students’ listening performance after the treatment. The mean score increased from 82.9 in the pretest to 86.7 in the post-test, while the maximum score rose from 88 to 94. Although some variation in improvement was observed, overall results indicate that the combined use of top-down and bottom-up strategies effectively enhanced students’ listening comprehension. These findings suggest that integrating both approaches can support EFL learners in developing more accurate and efficient listening skills.